EFFECT OF AMMONIUM SULPHATE ON HAEMATOLOGY PROFILE IN Channa punctaus (BLOCH.) (International Journal of Food and Nutritional Sciences, 2023)
The current study undertaken was the haematological profile changesin the snakehead fish Channa punctatus induced to sublethal concentration (16.5 mg/L) of inorganic fertilizer, ammonium sulphate for chronic (30 days). The treated fishes showed very significant changes at the haematological levels various parameters such as Hb, RBC, WBC decreases while in DLC, Neutrophil, Monocytes and Eosinophil values increase. The present study revealed a severe physiological dysfunction in response to Ammonium sulphate toxicity in the fish Channa punctatus (Bloch.). So, it is suggested that more appropriate condition to culture at water fertilizer, ammonium sulphate concentration of less than 16.5 mg/L in fish culture pond for optimum growth performance.